2007
DOI: 10.1037/0735-7028.38.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists' knowledge and attitudes about fetal alcohol syndrome, fetal alcohol spectrum disorders, and alcohol use during pregnancy.

Abstract: Do you have adequate knowledge of the hallmarks of fetal alcohol syndrome and fetal alcohol spectrum disorders? Can you identify pregnant women who are at risk for having a child with the disorder? A large random sample survey of American Psychological Association members uncovered large deficits in psychologists' knowledge about the diagnosis, treatment, and prevention of these problems. The authors report accurate information about these damaging disorders and identify the errors most commonly demonstrated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Research highlights a lack of knowledge and understanding of FASD in trainees and professionals across medical, mental health, educational, legal, and child welfare fields [11,19, 22-26]. A few brief survey studies have documented adequate basic knowledge of FASD across professions [27-28]; however, several studies suggest that while providers may have basic knowledge about FASD, they often have difficulty applying this information when implementing services [28-29].…”
Section: Discussionmentioning
confidence: 99%
“…Research highlights a lack of knowledge and understanding of FASD in trainees and professionals across medical, mental health, educational, legal, and child welfare fields [11,19, 22-26]. A few brief survey studies have documented adequate basic knowledge of FASD across professions [27-28]; however, several studies suggest that while providers may have basic knowledge about FASD, they often have difficulty applying this information when implementing services [28-29].…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate diagnosis and treatment of FASDs, it is imperative that professionals working in health care, education, social services, and the criminal justice system are properly trained in how to recognize individuals with PAE and educated regarding appropriate interventions for this population [Gahagan et al, 2006;FASD Regional Training Centers Consortium, 2007;Wedding et al, 2007;Mutch et al, 2009;Paley et al, 2009]. In some cases, it may also be important to change the attitudes of professionals who come in contact with and provide services to alcohol-exposed individuals and their families.…”
Section: Recommendations and Future Directionsmentioning
confidence: 99%
“…However, reluctance of health professionals to do this, possibly because of the perceived "moral" overlay to the consumption of alcohol, has been well documented (Wedding et al, 2007) and similar reservations are likely to affect colleagues in education.…”
Section: Discussionmentioning
confidence: 95%
“…A 2003 survey by the American Psychological Association of practising psychologists in the United States revealed that 81% of respondents believed (incorrectly) that alcohol withdrawal at birth was the worst consequence of prenatal exposure to alcohol (cited in Wedding et al, 2007). MacKinnion, William-Avery, and Pentz (1995) used questionnaires in school surveys to ask over 4000 teenagers about their knowledge and understanding of FASD.…”
Section: Why Is Fasd Under Reported?mentioning
confidence: 98%